IMPLEMENTASI KEBIJAKAN PROGRAM PENGELOLAAN SAMPAH DI SIGLI KABUPATEN PIDIE - Ricky Muliawan Hansyar; Halimah Halimah (Jurnal Sains Riset, 2022)
The implementation of the waste management program policy at the Pidie Regency Environment Service has not been carried out optimally, because there is still a lot of garbage piled up in Sigli. Temporary waste collection points provided by the government are not commensurate with the volume of waste available. The focus of this research it the implementation of waste management program policies based on the variables of communication, resources, disposition, and bureaucratic structure at the Pidie District Environmental Service and obstacles in implementing waste management program policies at the Pidie District Environmental Service. The approach used in this research is a qualitative research approach. Data collection techniques used are observation, interview and documentation. Meanwhile, the data analysis technique uses an interactive analysis model. The result of thr study show that waste management is still carried out using conventional systems, namely collection, removal and disposal even thought there is Law No. 18 of 2008, Government Regulation No. 81 of 2012 and also Pidie Regency Qanun No. 6 of 2012 concerning waste management.Keywords : Implementation, Policy, Program, Management, Waste